Particle size grouping method as a control system of efficiency flotation process on the example of coal - Kalisz D.; Kuglin K.; Młynarczykowska A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Agglomeration of coal particles during flotation can be analysed with the Particle Size Grouping (PSG) method. Numerous experiments were carried out to theoretically explain the effect of carbon particles agglomeration, but the result still remains incomplete. In this paper the PSG method was used to analyse agglomeration groups of carbon particles of initial size 100-400 μm, maintaining the total particle volume. The size of particles population with definite radius and density was determined for 1 Mg coal. The influence of density and size of particles with given mixing energies and parameter α on agglomeration was analysed. It was stated that the size of the particles had an effect on their agglomeration. In the analysed cases the dimensionless parameter of collision turbulence t* needed for particles agglomeration in particular size groups was importantly shorter for particles of initial size 300 and 400 μm. The change of the mixing energy did not have influence on the agglomeration of coal particles. The theoretical analyses based on computer calculations were supplemented by the analyses of the coal flotation process on an aqueous model. Experiments lied in introducing a foaming agent in the form of aqueous solution of hexanol which, without changing pH of the pulp, lowered surface tension value, and consequently increased the dispersion of air in the suspension. The experimental results were presented in the form of flotation kinetics curves. Fine particles 100-200μm. turned out to be best for flotation, unlike coarse 400-500 μm.